By SAScongruence rule Triangles DFE and ACB are Congruent.
Twoangles and a non-included side of a triangle are said to be congruent when they are equivalent to the corresponding angles and sides of another triangle.
The measurements of the sides and angles of two or more triangles determine their congruence. A triangle's size is determined by its three sides, and its shape is determined by its three angles. Two triangles are said to be congruent if the pairings of their respective sides and angles are equal.
We have Two Triangles DFE and ACB.
Now, from the triangles we have
AC = DF
BC = EF
< ACB = < DFE
and, the angle which is congruent is in between two congruent sides.
So, by SAS congruence rule Triangles DFE and ACB are Congruent.
Learn more about congruence rule here:
#SPJ7
Answer:
You can use the Side-Angle-Side Postulate.
Step-by-step explanation:
The Side-Angle-Side (or SAS) Postulate basically states that if two sides of two triangles and the included angle are congruent, the two triangles are congruent.
The exponential growth rate is approximately 1.56% per year for a population to double in 45 years.
To calculate the annual growth rate for a population that doubles in a specific time period, we can use the rule of 70, which is a formula for estimating the time it takes for an investment or population to double given a constant growth rate. The rate of growth (r) can be calculated as r=70/t, where t is the time in years.
In this case, the country's population doubled in 45 years. So, the annual growth rate would be r=70/45
= 1.56%.
Therefore, the exponential growth rate that caused the country's population to double in 45 years is approximately 1.56% per year.
#SPJ1
901
ILY EPICFARTS2021 THANKS FOR ALL THE POINTS
The given function is
f(x)= log 10 x
Taking base as 10
→→Using the property of, log a b= log a + log b
→y = 1 + as,
we have to approximate the value of y in the equation
→10 y = 6
→y=
= 1 +
=
x= ==0.398
Solving graphically,
we get , x= 0.398 for , y= =.6
9514 1404 393
Answer:
2 and 3
Step-by-step explanation:
Let x and y represent the first and second numbers, respectively.
3x +3y = 15
4x +2y = 14
Dividing the equations by common factors, we can rewrite them to standard form:
x + y = 5
2x + y = 7
Subtracting the first equation from the second gives ...
(2x +y) -(x +y) = (7) -(5)
x = 2
Using either equation to find y, we have also ...
y = 3
The two numbers are 2 and 3.
Answer:
{3m+3n=15
4m+2n=14
Step-by-step explanation: